Psychiatric profile of patients with alcoholism - L., Versi; M., Umashankar (International Journal of Research in Medical Sciences, 2017)
Background: The overall personality is related to the treatment outcome. Hence for successful treatment and management of alcohol dependent cases, it is essential to understand their personality. Objective was to study the psychiatric profile of patients with alcoholism. Methods: Present cross sectional hospital based study was conducted for six months in department of psychiatry, Institute of mental health, Hyderabad, a tertiary care psychiatric facility. This 600 bedded hospital has a daily outpatient clinic and provides inpatient care. Alcohol dependence syndrome and uncomplicated withdrawal state patients only were included in the present study. Age less than 18 and more than 60 years, patients with mental retardation, patients with personality disorders were excluded. Results: Majority of subjects belongs upper low socioeconomic status 57.50% (n=23), 36 (90%) were Hindus, two (5%) were Muslims and two (5%) were Christians. 42.5% (n=17) were illiterate, 22.5% (n=9) were having primary school education. 12.5% (n=5) were single, 87.5% (n=35) were married. 77.5% (n=31) were unskilled, 17.5% (n=7) were semiskilled, and 5% (n=2) were skilled. Maximum were from rural areas (67.5%) and 32.5% were from urban areas. self-injurious behavior is female and males are same 25% (n=5). Majority of males in the high-risk level of severity of alcoholism has banging head against something, to the extent that caused a bruise to appear type of behavior. Conclusions: Majority alcoholics were from low social classes, were illiterate, were married, unskilled workers. Hence these group people should be paid proper attention to prevent the occurrence of alcoholism among them.